A magnetic measurement technique for small rare samples: Pre-study for Chang’e-5 returned and other extraterrestrial samples - Hou, Yifei; Zhang, Min; He, Kuang; Shen, Zhongshan; Dong, Liang; Fan, Yunchang; Qi, Kaixian; Liu, Shuangchi; Cai, Shuhui; Qin, Huafeng (Frontiers in Earth Science, 2023)
Standard-size samples are usually used for traditional paleomagnetic study. In some cases, tiny irregular samples are employed considering their amount and magnetic strength as well as experiment efficiency. With the development of deep space exploration, the demand for studying tiny and magnetic weak samples is increasing. In this study, we established a magnetic measurement technique for tiny rare samples. We designed low-background, sample-nondestructive and high-flexibility holders with various materials for different measurements of tiny samples. With the customized holders, we estimated uncertainty and reliability of magnetic measurements of small specimens from a terrestrial basalt. The results indicate that susceptibility and remanence of tiny specimens (e.g., 2-mm cubes) are more affected by measurement position than larger specimens ( 5 mm), which reminds us to pay special attention to consistency of the tiny specimen position during series of measurements. Moreover, susceptibility and remanence of small sister specimens (2-mm and 5-mm cubes) are more scattered than those of large ones (cube length  1 cm), mainly due to inhomogeneity of magnetic mineral abundance in the sample. Nevertheless, the average magnetic results of different-size specimens are generally consistent within error, indicating the inhomogeneity of small specimens can be averaged out and demonstrating the reliability of small samples during magnetic measurements. Finally, we tested our measurement system with a lunar meteorite, which mimics the Chang’e-5 returned samples in both size and mineralogy. The main minerals of the meteorite are plagioclase, pyroxene, troilite and kamacite. The IRM normalized paleointensity method recovered the expected laboratory field while the ARM corrected paleointensities are about 2-3 times the expected field, where the latter can be explained by inapplicability of the empirical f to the meteorite specimens. The ARM and IRM paleointensity calibration factor f and a of the lunar meteorite were calculated to be 3.89 and 3138 μT, respectively, which provides new constraints for the empirical values. The magnetic results of the lunar meteorite demonstrate the efficiency of our measurement system for tiny weak samples. This study provides technical support for paleomagnetic study of the Chang'e-5 and other extraterrestrial samples in the future.